Disruption and Disposition in Lifelong Learning - Edwards, Anne; MacKenzie, Lin; Ranson, Stewart; Rutledge, Heather (Outlines. Critical Practice Studies, 2002)
UK government policies for social inclusion through engaging with the learning society aim at repositioning people as capable participants in their social worlds. These policies at first sight appear to be aimed at a sophisticated restructuring of social contexts as well as at an enhancing of individual learning. However there is a degree of conceptual confusion within these policies. In this paper we explore some of the tensions evident in a study of a family learning centre in an English city. In the exploration we examine the extent to which the tools offered by sociocultural and activity theory (SAT) can assist in resolving that conceptual confusion and how SAT itself might need to develop in order to analyse complex and sustained forms of intervention.